2022
DOI: 10.3233/shti220375
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Facilitators of Using Smartphones in Educational Activities: Medical and Nursing Students’ Perspective

Abstract: Background: Todays, smartphone technologies and applications are used in the medical and nursing fields. Medical and nursing students are among the groups in which the use of these tools is observed. Objectives: To investigate their views on the barriers and facilitators of the use of these technologies. Methods: Four hundred people (200 people from each group) were invited randomly. A questionnaire was used to collect data. To collect data, hospitals were referred and the questionnaires were provided to stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…The development of a wireless handheld probe has made the use of ultrasound for anatomy teaching a feasible option across educational institutions due to their relatively low price point and portability. Furthermore, the wireless connection between the probe and a smartphone or tablet provides familiarity to the students (Sheikhtaheri et al, 2018), and allows increased accessibility to students with a limited knowledge of US knobology.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a wireless handheld probe has made the use of ultrasound for anatomy teaching a feasible option across educational institutions due to their relatively low price point and portability. Furthermore, the wireless connection between the probe and a smartphone or tablet provides familiarity to the students (Sheikhtaheri et al, 2018), and allows increased accessibility to students with a limited knowledge of US knobology.…”
Section: Introductionmentioning
confidence: 99%
“…The nursing information smartphone enabled the students to immediately retrieve patient records, access medical resources, and provide appropriate responses to parent queries. Sheikhtaheri et al 12 also examined the educational benefits of personal smartphones from the perspective of nursing students and showed that the use of relevant technologies saved time, allowed students to promptly access patient records, and facilitated positive learning attitudes. The present study validates the educational benefits of mobile technologies for nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the heavy workloads, assignments, caring for patients, academic demands, and the clinical environment have been identified as significant contributors to stress among nursing students. 10 Although nursing students often use personal smartphones during clinical nursing practicums for instant access to various digital resources, including nursing diagnosis, pharmacology, laboratory, and MEDLINE databases, to facilitate learning, 11,12 personal smartphones could not provide immediate access to information on hospitalized patients' health conditions. The present study was undertaken in a regional teaching hospital in Central Taiwan, and the hospital had used mobile nursing stations in clinical care for several years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their swift integration into everyday life has provided clear benefits across many areas of society [1]. In education, mobile phones offer the ability to enrich learning, promote collaboration between students and teachers, and provide flexibility in managing coursework [2,3]. This easy access allows students to connect with classmates, tap into learning resources, and engage with academic support systems, thus fostering a more dynamic educational experience [4].…”
Section: Introductionmentioning
confidence: 99%